Segmenting eWOM Seekers in Tourist Destinations: Communication Dynamics in Czechia and Slovakia - Kristína Pompurová,; Kristína Medeková,; Eva Zabudská, (Communication Today, 2025)
This study explores the segmentation of electronic word-of-mouth (eWOM) seekers in tourist destinations, with a specific focus on communication preferences and channels. The aim is to enhance the understanding of eWOM behaviour beyond traditional sociodemographic factors, emphasising communication strategies that influence consumer decision-making in selecting tourist destinations. Using data from an electronic survey completed by respondents in Czechia and Slovakia, cluster and factor analyses identified four main segments of eWOM seekers: eWOM Enthusiasts, Local Explorers, Global Influencer-Focused Travellers, and Authenticity-Seeking Globetrotters. The study further examines preferred communication channels, including key travel information hubs, influencer-led networks, and supplementary channels to tailor marketing strategies to specific segments. Findings provide valuable communication insights for destination marketers, offering a framework for future research on effectively leveraging eWOM in tourism marketing.